Pengaruh Lama Waktu Fermentasi terhadap Kandungan Asam Phytat, Kecernaan Bahan Kering dan Bahan Organik Dedak Padi secara In Vitro - Tandang, Mariano D.; Oematan, Gustaf; Lestari, Gusti A. Y. (Animal Agricultura, 2024)
The aim of this research was to determine the effect of long fermentation time for rice bran on phytic acid content, dry matter digestibility and organic matter. The method used in this research was an experimental method with a completely randomized plan (CRD) of 5 treatments and 5 replications so that there were 25 experimental units, consisting of LF0: 0 days fermentation time, LF2: 2 days fermentation time, LF4: 2 days fermentation time. long fermentation time 4 days, LF6: long fermentation time 6 days, LF8: long fermentation time 8 days. The parameters taken are phytic acid content, dry matter digestibility (KcBK) and organic matter (KcBO). The results obtained statistically stated that the fermentation time of up to 8 days showed the same results or had a significant effect (P<0.05) on the digestibility of dry matter and organic matter and had no significant effect (P>0.05) on the phytic acid content. The conclusion that can be drawn is that different fermentation times for rice bran can increase the digestibility of dry matter and organic matter in vitro even though the phytic acid content obtained is the same.